Dampak Alih Fungsi Lahan Pertanian Terhadap Kondisi Sosial Ekonomi Petani (Studi Kasus Pembangunan Jalan Tol Surakarta – Yogyakarta Di Kabupaten Boyolali - Riptanti, Erlyna Wida; Raharjo, Zeino Heka; Khairiyakh, Refa’ul (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
This paper aims to examine the effect of changes in the function of agricultural land on the socio-economic situation of farmers and to understand the social dynamics that occur when there is a change in the function of agricultural land, as well as identify the factors that encourage or inhibit the conversion of agricultural land into toll roads in Banyudono and Sawit District, Boyolali Regency. This study used a qualitative research method with a case study approach. Data collection techniques through observation, interviews, and documentation. Data analysis were carried out through data reduction and presentation to draw conclusions. Purposive sampling technique was used to select informants. The results of the study show that the change in the function of agricultural land into toll roads has social impacts, such as disruption of irrigation canals and resulting in a large number of dry lands. In addition, the economic impact can also be seen from the reduced yields because some of the land has been con erted. During the construction of the toll road, there was a change in people's livelihoods because they used the compensation they received to open new businesses.